Aztreonam plus ceftazidime-avibactam as treatment of NDM-1-producing Klebsiella pneumoniae bacteraemia in a neutropenic patient: Last resort therapy? - Bocanegra Ibarias, Paola; Camacho Ortiz, Adrián; Garza González, Elvira; Flores Treviño, Samantha Maribel; Kim, Hyojin; Pérez Alba, Eduardo (Elsevier, 2020)
Objectives: We report the successful treatment of a bloodstream infection caused by Klebsiella pneumoniae harbouring NDM-1 using aztreonam-ceftazidime-avibactam in a neutropenic patient in whom colistin and meropenem therapy had previously failed.